The Sexual Health of Transgender Men: A Scoping Review. Issue 4 (13th June 2017) - Stephenson, Rob; Riley, Erin; Rogers, Erin; Suarez, Nicolas; Metheny, Nick; Senda, Jonathan; Saylor, Kate M.; Bauermeister, José A.
Abstract : There is a general paucity of research concerning the sexual health of transgender individuals, and most existing research focuses on transgender women. A scoping review concerning the sexual health of transgender men was conducted to identify gaps in the literature and to highlight opportunities for future research and intervention. A comprehensive search of seven databases was conducted. The Joanna Briggs Institute Reviewers' Manual was used as a framework. Some 7, 485 articles were initially identified using a search strategy applied to seven online databases: 54 articles were identified as relevant to the research questions and reviewed in detail; of those, 33 were included in the final analysis. Studies were conceptualized into four broad themes: sexual behaviors, sexual identity, sexual pleasure and sexual function, and transactional sex. Besides an overall lack of research, existing studies were often characterized by small convenience samples that do not allow for generalization to the larger population of transgender men. Significant gaps in the literature regarding sexual coercion, sexual and intimate partner violence, and relationship quality and functioning among transgender men exist. There is a need to improve the scope and depth of research examining the sexual health of this population, especially concerning sexual risk behaviors and structural barriers to sexual health care access.